Comprehensive analysis of post‐diagnostic prostate‐specific antigen kinetics as predictor of a prostate cancer progression in active surveillance patients. (15th June 2012) - Iremashvili, Viacheslav; Manoharan, Murugesan; Lokeshwar, Soum D.; Rosenberg, Daniel L.; Pan, David; Soloway, Mark S.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? A significant proportion of patients diagnosed with prostate cancer do not require immediate treatment and could be managed by active surveillance, which usually includes serial measurements of prostate‐specific antigen (PSA) levels and regular biopsies. The rate of rise in PSA levels, which could be calculated as PSA velocity or PSA doubling time, was previously suggested to be associated with the biological aggressiveness of prostate cancer. Although these parameters are obvious candidates for predicting tumour progression in active surveillance patients, earlier studies that examined this topic provided conflicting results. Our analysis showed that PSA velocity and PSA doubling time calculated at different time‐points, by different methods, over different intervals, and in different sub‐groups of active surveillance patients provide little if any prognostic information. Although we found some significant associations between PSA velocity and the risk of progression as determined by biopsy, the actual clinical significance of this association was small. Furthermore, PSA velocity did not add to the predictive accuracy of total PSA. Objective To study whether prostate‐specific antigen (PSA) velocity (PSAV) and PSA doubling time (PSADT) are associated with biopsy progression in patients managed by active surveillance. Patients and Methods Our inclusion criteria for active surveillance are biopsy Gleason sum <7, two or fewer positive biopsy cores, ≤20% tumour present in any core, and clinical stage T1–T2a. Changes in any of these parameters during the follow‐up that went beyond these limits are considered to be progression. This study included 250 patients who had at least one surveillance biopsy, an available PSA measured no earlier than 3 months before diagnosis, and at least one PSA measurement before each surveillance biopsy. We evaluated the association between PSA kinetics and progression at successive surveillance biopsies in different sub‐groups of patients by calculating the area under the curve (AUC) as well as sensitivity and specificity of different thresholds. Results Over a median follow‐up of 3.0 years, the disease of 64 (26%) patients progressed. PSADT was not associated with biopsy progression, whereas PSAV was only weakly associated with progression in certain sub‐groups. However, incorporation of PSAV in models including total PSA resulted in a moderate increase in AUC only when the entire cohort was analysed. In other sub‐groups the predictive accuracy of total PSA was not significantly improved by adding PSAV. Conclusions Our findings confirm that PSA kinetics should not be used in decision‐making in patients with low‐risk prostate cancer managed by active surveillance. Regular surveillance biopsies should remain as the principal method of monitoring cancer progression in these men.